Infectious diseases : emergence and re-emergence : a geographical analysis - Cliff, A. D. (Andrew David); Smallman-Raynor, Matthew (Oxford geographical and environmental studies., 2009)
The last four decades of human history have seen the emergence of an unprecedented number of 'new' infectious diseases: the familiar roll call includes AIDS, Ebola, H5N1 influenza, hantavirus, hepatitis E, Lassa fever, legionnaires' and Lyme diseases, Marburg fever, Rift Valley fever, SARS, and West Nile. The outbreaks range in scale from global pandemics that have brought death and misery to millions, through to self-limiting outbreaks of mainly local impact. Some outbreaks haveerupted explosively but have already faded away; some grumble along or continue to devastate as now persistent featu.